Stability Analysis of Binary Solvent Mixtures for Herbal Phytochemical Extraction (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
Most of the extraction processes of herbal phytochemicals use solvent mixtures as a phytochemical transfer mediums. It is very important to predict the stability of solvent mixtures before it is used to extract herbal phytochemicals. In order to prevent any disturbance in the herbal extraction, the solvent mixtures must be in a single liquid phase (miscible to each other). In this study, the stabilities of five binary solvents (methanol-water, methanol-ethyl acetate, methanol-acetic acid, methanol-n-propionaldehyde, and methanol-isobutyraldehyde mixtures) that could be used in the current extraction processes are evaluated. The main purpose of this study is to evaluate these binary solvents in terms of their stability using Gibbs energy of mixing. The value of the function ?Gmix/RT is calculated for each solvent mixture. Then, the graph for ?Gmix/RT versus solvent molar fraction x is plotted. From this plot and the value of function ?Gmix/RT, it can be concluded whether the solvent mixtures are stable or unstable. From the analysis, all five binary mixtures are stable within the selected molar fraction making all mixtures are suitable to be applied in herbal extraction.